REKONSTRUKSI KONSEP EVALUASI PENDIDIKAN RASULULLAH SAW DALAM MEWUJUDKAN REPARASI PENDIDIKAN DI INDONESIA - Maulidi, Ahmad Riyadh (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2022)
The practice of evaluating education in Indonesia that has been carried out so far has not been able to deliver Indonesia to a good quality of education. Various problems and problems, especially related to evaluation, are still found in the implementation of education in the country. As a result, the goals of education are difficult to achieve. Thus, a reconstruction of education evaluation is needed in order to repair existing education in Indonesia. Reflecting on the practice of evaluating the style of the Prophet. which applies the principles of comprehensiveness and continuity, was able to bring the Arab society which was once known as a society with low morals to become a civil society that is famous throughout the world. It is interesting for researchers to formulate how to reconstruct the evaluation concept. in order to answer various problems of evaluating education in Indonesia. This research method uses the library method. The results of the study indicate that the evaluations carried out in Indonesia so far have only reached the theoretical level. In contrast to the evaluation carried out at the time of the Prophet Muhammad. who have really used the principles of comprehensiveness and continuity well. Good results are in the evaluation of the Prophet Muhammad SAW. This is considered necessary to be reconstructed in order to produce a reparation for education in Indonesia. The trick is to hold fast to these two principles and look for alternatives so that the essence of evaluation practice is at the time of the Prophet Muhammad. can be applied in Indonesia.